Sensor acquired reachable workspace in the elderly population: A cross-sectional observational study - Chan, Vicky; Thai, Richard; Vartanian, Revik; Kim, Min Su; Hatch, Maya N.; Koh, Jason; Han, Jay J. (Medicine (Baltimore), 2022)
The elderly population experiences a decline in upper extremity range of motion (ROM), impairing activities of daily living. The primary mode of quantification is by goniometer measurement. In this cross-sectional observation study, we investigate a sensor-acquired reachable workspace for assessing shoulder ROM decline in an elderly population in comparison to traditional measurements. Sixty-one healthy subjects aged ≥ 65 years were included and compared to a cohort of 39 younger subjects, aged 20 to 64. A sensor acquired reachable workspace using a Kinect motion capture camera measured the maximum reaching ability of both arms while in a seated position, measured in m 2 and normalized to arm length to calculate a novel score defined as a relative surface area. This score approximates range of motion in the upper extremity. This measurement was compared to goniometer measurements, including active ROM in shoulder flexion and abduction. Total RSA shows moderate to strong correlation between goniometer in flexion and abduction in the dominant arm ( R = 0.790 and R = 0.650, P < .001, respectively) and moderate correlations for the nondominant arm ( R = 0.622 and R = 0.615, P < .001). Compared to the younger cohort, the elderly population demonstrated significantly reduced total RSA in the dominant arm (mean elderly = 0.774, SD = 0.09; mean younger = 0.830, SD = 0.07, P < .001), with significant reductions in the upper lateral quadrant in both arms (dominantmean elderly = 0.225, SD = 0.04; mean younger = 0.241, SD = 0.01; P < .001; nondominantmean elderly = 0.213, SD = 0.03; mean younger = 0.228, SD = 0.01; P = .004). The test-retest reliability was strong for both dominant and nondominant total RSA (ICC > 0.762). The reachable workspace demonstrates promise as a simple and quick tool for clinicians to assess detailed and quantitative active shoulder ROM decline in the elderly population.